SPECTRAL AND TEXTURAL CHARACTERISTICS OF THE LOWLAND TROPICAL RAIN FOREST OF JAMBI, SUMATERA - UPIK ROSALINA WASRIN; MUCHLISIN ARIEF; SETIABUDHI SETIABUDHI (SEAMEO BIOTROP, 1999)
Analyses of Landsat TM and SPOT multispectral data were performed with a very detailed description of the vegetation cover in the field to get a relevancy and consistency of digital image classification in a semi-automatic approach. Three main vegetation types, i.e. primary forest, logged-over forest and secondary forest after clear cut were analyzed and the microclimatic parameters were also measured to describe the ecological condition of the vegetation. Spectral and textural analysis of data obtained from field measurements and spectral reflectance values of the remote sensing data are the main topic of this report as one aspect of study on the Digital Method of Detection and Monitoring on Forest Ecosystem Change Using High Resolution Satellite Data funded by the Indonesian National Research Council. This study shows that spectral reflectance values alone cannot differentiate the logged-over forest from the primary forest, but it is very sharply distinguished from the secondary forest. As for the texture analysis, it is possible to distinguish the logged-over forest from the primary forest, as shown by different values of degree of Entropy, although spatially, it is still doubtful. Key words: Indonesia/Jambi/Tropical rain forests/lowland areas/Remote sensing/Vegetation Analysis/ Logged-over forests/Primary forests/Secondary forests.